2015
DOI: 10.1177/000313481508100431
|View full text |Cite
|
Sign up to set email alerts
|

You Cannot Go Home: Routine Concussion Evaluation is not Enough

Abstract: Traditional care of mild traumatic brain injury (MTBI) is to discharge patients from the emergency department (ED) if they have a Glasgow Coma Score (GCS) of 15 and a normal head computed tomography (CT) scan. However, this does not address short-term neurocognitive deficits. Our hypothesis is that a notable percentage of patients will need outpatient neurocognitive therapy despite a reassuring initial presentation. This is a retrospective review of patients with MTBI at an urban Level I trauma center. Inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Hartwell et al ( 2015) 9 . This retrospective study identified 901 patients (age 14 to 93 years ) classified as mild TBI from a trauma registry of 6032 patients admitted to the trauma center between July 2010 and December 2011.…”
Section: Joseph Et Al (2014)mentioning
confidence: 99%
“…Hartwell et al ( 2015) 9 . This retrospective study identified 901 patients (age 14 to 93 years ) classified as mild TBI from a trauma registry of 6032 patients admitted to the trauma center between July 2010 and December 2011.…”
Section: Joseph Et Al (2014)mentioning
confidence: 99%
“…Many patients who suffer blunt head trauma are at risk of traumatic brain injury (TBI). This affects approximately two million people in the USA each year [ 1 ]. In addition, there are 1.4 million annual hospitalizations for TBI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%